Mapeamento de como profissionais da Educação Infantil entendem e ofertam a Educação Física para crianças de 0 a 3 anos - Sales, Karina Polezel de (Universidade Federal de São Carlos, 2023)
Physical Education, integrated into the school’s pedagogical proposal, is a curricular component of Basic Education, adjusting to the age groups and conditions of the school population. Although mandatory, the generic wording of the legislation does not ensure the subject’s presence in the Basic Education stages. This legislation does not guarantee that classes will be taught by professionals with a specialization, nor does it assure that students will have access to the study object and knowledge expressed in the most diverse components of corporal movement culture. As a result, in many educational institutions, especially in childhood education, the particular contents related to Physical Education end up blended with other knowledge developed and proposed by teachers specialized in Pedagogy or Primary Teaching. Considering the importance of providing appropriate activities for children according to their age group and that these activities are fundamental for their complete development, we envision the presence of specialist professionals in a childhood education as essential to enhance child development and movement. However, in addition to a few studies related to the age group and Physical Education in childhood education, especially from zero to three years old, there is no mention of the subject in the primary official documents drawn up by the Federal Government published to date. As such, the purpose of this study was to map and investigate, in collaboration with early childhood education professionals, how Physical Education was understood and delivered to children aged zero to three. Based on our reflection and the literature review, we propose a set of experiences for professionals working with this age group to contribute to their practices related to the body and movement. Throughout the study, we analyzed which contents and strategies the professionals used to work with Physical Education and what are the main difficulties faced by them. We concluded that professional qualification, both initial and continuing education, has been the greatest difficulty. The majority of research participants believe that it is insufficient to meet the educational needs of children aged zero to three. It was also concluded that Physical Education was understood mainly by its motor skills, disregarding its scope of action. It also discussed the presence of a specialized professional and how they could contribute to the children’s development, ensuring a better quality in meeting the needs of children from zero to three years old, an opinion shared by most of the research participants. In conclusion, this study expands the debate on the presence of Physical Education in institutions attending children from zero to three years old because it is hardly found in academia and within the schools themselves.
Mapping how early education professionals understand and offer physical education to children from 0 to 3 years old
Keywords: Educação física; Educação infantil; Physical education; Childhood education; Zero to three years; Zero a três anos; CIENCIAS DA SAUDE::EDUCACAO FISICA